Drying and essential oil extraction of Brazilian peppertree (Schinus terebinthifolius Raddi) fruits - Julia L. Governici; Naiara C. Z. Sperotto; Evandro de C. Melo; Diego A. Gonzaga; Antônio P. S. Carneiro (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objectives of this work were to determine the effect of the drying air temperature and fruit fragmentation on the essential oil yield of Brazilian peppertree (Schinus terebinthifolius) fruits, to model drying curves, and evaluate the energy consumption of the drying process. The study was conducted in Viçosa, MG, Brazil, in May 2018. The experiment was conducted using a completely randomized design, in a 3 x 2 factorial arrangement (3 drying air temperatures and 2 fruit fragmentation types), with three replications. Whole fruits (350 g) were dried at 50, 60, and 70 °C until the water content reached a water content of 0.11 on dry basis; 90 g of these fruits where kept in the dryer until reaching an equilibrium water content for the modeling. The data of drying were fitted to 12 mathematical models, whose performances were evaluated by the coefficient of determination, mean relative error, mean estimated error, and residue distribution. The essential oil was extracted by hydro-distillation using whole or fragmented fruits. Fruits dried at 50 °C and fragmented before extraction had higher essential oil yield. The use of air temperature of 70 °C resulted in lower drying time and energy consumption. The data fitted to the Midilli model satisfactorily, regardless of the drying air temperature.